MINUTES OF ENGLISH SONGS PROGRAM IN ENHANCING ELEMENTARY SCHOOL STUDENTS’ VOCABULARY SIZE - Dari, Tita Ratna Wulan; Sholikhah, Hani Atus; Alrefi, Alrefi; Izzah, Fathimah Nurul (LPPM Univ. Ibn Khaldun Bogor, 2024)
The ‘Minutes of English Songs’ program aimed at helping teachers in maximizing students' vocabulary acquisition in primary schools. Through a music-based learning method, it was designed using English children's songs with simple lyrics to introduce new vocabulary in a contextual and fun way. This activity involved students of SDN 1 Talang Kelapa as participants of the Community Service activity in understanding, remembering, and applying vocabulary through structured activities, including singing, translating lyrics, moving limbs, repeating lyrics, and multiple-choice question exercises. A quasi-experimental method was used to evaluate the effectiveness of the program, with a pre-test and post-test to measure the improvement in students' vocabulary acquisition. The results of the program showed that there was a significant improvement in students' vocabulary skills after attending the program, with an average pre-test score of 55%, which increased to 85% in the post-test. In addition to vocabulary improvement, students also showed increased confidence in speaking English and had positive perceptions of the program. The findings suggested that a music-based approach can be an effective alternative in teaching English vocabulary at the primary school level. The program is expected to be applied more widely as an innovative effort to improve students' vocabulary acquisition in a fun way.